History, gravity and international finance - Barry Eichengreen; Arnaud Mehl; Livia Chiţu (European Central Bank (ECB), 2012)
We analyze persistence in patterns of bilateral financial investment using data on US investors' holdings of foreign bonds. We document a “history effect” in which the pattern of holdings seven decades ago continues to influence holdings today. 10 to 15% of the cross-country variation in US investors' foreign bond holdings is explained by holdings 70 years ago, plausibly reflecting fixed costs of market entry and exit. This effect is twice as large for bonds denominated in currencies other than the dollar, suggesting the existence of even higher fixed costs of initiating US foreign investment in currencies other than the dollar. Our findings point to history and path dependence as key sources of financial market segmentation.
Keywords: F30; N20; 330; geography of asset holdings; Gravity Model; Hysteresis; International Finance; international role of the dollar; Persistence